Mainstreaming Efficient Legume Seed Systems in Eastern Africa: Challenges, opportunities and contributions towards improved livelihoods - Ojiewo, Christopher Ochieng; Rubyogo, Jean-Claude; Wesonga, John; Bishaw, Zewdie; Abang, Mathew M.; Gelalcha, Solomon (Food and Agriculture Organization of the United Nations, 2018)
Legumes are important components of sustainable farming systems. They are useful to diversify and intensify cropping systems as double, catch, relay and intercrops; fix ‘free’ nitrogen to soils from the atmosphere and improve soil health that boost cereal crop yields; act as rotation crops for breaking disease and pest cycles; increase and diversify smallholder incomes (and hence buffer them from the effects of price, pest and climate-related production fluctuations); enhance quality of household diets because of their higher protein and micro-nutrient content compared with starch-based staple cereal crops; and provide good sources of animal feed (high protein crop residues and byproducts) and low carbon footprint, mitigating climate change...